Caring for the carers - Myth or reality? Social and personal resources amongst perioperative nurses. - Michael, Rene (Cambridge Publishing, 2002)
The importance of social and personal support resources in assisting individuals to overcome the impact of work related trauma has long been recognised. Support resource are capable of responding aprropriately to the influence of recovery dynamics in a contingent manner. The quality of recovery from trauma is suggested to be dependent on the interactive processes of the individuals, teh organisational environment they work in and the support provided.Social and personal resources are a central component of several devices that are used to assist recovery from work related trauma. Therefore, investigation of the relationship between support needs, support providers and the nature and content of support interventions is required.Using a two pronged approach of quantitative and qualitative methods, 213 nurses working in rural and metropolitan operating suites were surveyed to assess the types, amount and effectiveness of social and personal resources that were used following exposure to traumatic work experiences. The findings demonstrate the significance of personal and social support resources in assisting periopeartive nurses to recover from traumatic experiences. A personal sense of coherence and emotional support received through disclosure to work colleagues and supervisors were the most salutary aspects of support following trauma.The results indicate that the work organisation needs to be educated in the need for and process of creating sanctuary and providing a holistic approach to management. Moreover, opportunities should be made avaiable through peer support programmes, educational programmes and professional meetings to better prepare nurses for traumatic sutuations and their aftermath. This will then allow perioperative nurses to continue to funcation at an acceptable level during the mitigation of work related trauma.